Cypermethrin Insecticide Induced Histopathological Alteration in Testis and Ovary of Males and Female Mice - Alaa S.Kathim; Saphia Al –Aitte (Zien Journals, 2022)
The present study sought to verify the effect of chemical pesticide Pyrethriod, cypermethyreien on the histopathological alteration in reproductive system such as testis and ovary organs of both sex, males and female mice.
Keywords: female; testis; males; reproductive